Vertical separation as a defense against strong suppliers - Noriaki Matsushima; Tomomichi Mizuno (Osaka University, Institute of Social and Economic Research (ISER), 2009)
We provide a simple model to investigate decisions about vertical separation. The key feature of this model is that more than one input is required for the final product of the downstream monopolist. We show that as the bargaining powers of independent complementary input suppliers grow larger, the downstream monopolist tends to separate from its input units. The results are related to a visible difference between the vertical structures of Japanese and US auto assemblers.
Keywords: L13; L22; M11; 330; Multiple inputs; Bargaining; Disintegration; Double marginalization